2015
DOI: 10.3390/wevj7020187
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Axial Flux Motor Technology for Hybrid Powertrain Integration

Abstract: Axial flux (AF) motors and generators have been used in niche automotive applications for many years. Given their disk like shape they offer distinct advantages for integration into hybrid powertrains where available length is limited. An overview of axial machine topologies is given and the design and performance laws that govern the sizing of axial flux permanent magnet machines are presented. Based on the analytical laws described it is shown that an axial machine can achieve significantly more torque than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The AF PMSM topology was described in detail in [27]. Figure 2a represents the shape of the motor disk, consisting of a single rotor sandwiched between two stators, where two sets of three phase windings are connected in parallel.…”
Section: Overview Of Motor Topology Assembly and Design Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The AF PMSM topology was described in detail in [27]. Figure 2a represents the shape of the motor disk, consisting of a single rotor sandwiched between two stators, where two sets of three phase windings are connected in parallel.…”
Section: Overview Of Motor Topology Assembly and Design Methodologymentioning
confidence: 99%
“…A three-phase PMSM, based on axial flux technology, that can be used in conjunction with custom-built or standard industrial inverters is shown in Figure 1a. Designed AFPMSMs combine high performance with reduced weight and size that are ideal for electric and hybrid electric vehicles [27][28][29]. These machines are characterized by the following key features: high torque and power density, low cogging torque, compact design with flat front and back faces for easy mounting, a through shaft, an integrated resolver for rotor position feedback; liquid cooling for enhanced performance.…”
Section: Experimental Measurementmentioning
confidence: 99%
“…Performance investigation was carried out on a number of AFMs from a low volume production line. The following AFM characteristics represent extended investigation of AFM performance of the earlier author's study (Mlot et al, 2018;Lamperth et al, 2015;Malloy et al, 2014). The measured values of motor performance were carried out on test rig (Figure 4).…”
Section: Performance Investigationmentioning
confidence: 99%
“…In the past decade, the technology of axial flux motors with permanent magnets was rapidly developed, with many improvements in automotive applications (Li et al, 2013;Woolmer and McCulloch, 2007;Lamperth et al, 2015;Malloy et al, 2014). High performance motors are suitable for a range of markets and applications, where weight and space are critical for the end-user.…”
Section: Afm Used In Automotive Applicationmentioning
confidence: 99%
“…[1]- [3]. Thanks to these features, they have been successfully applied to industrial fields, for instance, electric vehicle traction motor, cooling fan, aircraft drive, and submarine drive [4]. It is worthy to point out that the magnetic structure of the AFPMM has a strong three-dimensional (3-D) effect, viz., the magnetic dimension along the radial direction is different at each radius, which brings challenges for the motor design.…”
Section: Green Open Access Added To Tu Delft Institutional Repositorymentioning
confidence: 99%